How can we use mobile apps for disaster communications in Taiwan: Problems and possible practice - Sz Jie Sung (International Telecommunications Society (ITS), 2011)
The growth rate of global smart phone in 2010 is as high as 78.1%, showing that smart phone gradually becomes the mainstream in the mobile phone market. Smart phone has the function of installing applications, provides users with more diversified mobile value-added services and will change users' communication habits in the future. Mobile communication follows the development trend of 3G and WiMAX, make users can link with mobile software stores through internet, downloading all kinds of applications, which has provided human beings with more diversified information, and gradually changed people's living habits. With the widespread of smart phone in Taiwan and many mobile applications start to go popular in market, people are crazy about downloading mobile applications, and different applications create different types of communications. Within a trend of smart phone and massive mobile apps go popular in Taiwan, what can we do to apply these tools for disaster communications? And compare to other infrastructure-level support, is mobile app a feasible route for disaster communications? What is the possible uses and challenges.
Keywords: 330